Two female campers building a campfire - Unknown:::Creator::::::::::::
Photograph shows two female campers stacking wood in a fire pit for a campfire at the YWCA's Camp Ayun Mapu. It is being built in an area with bench seats circling the fire pit and the forest in the background.